DEMOCRATIZATION OF SCHOOL MANAGEMENT IN A MUNICIPALITY IN THE AMAZON REGION OF PARÁ: CHALLENGES, ADVANCES AND CONTRADICTIONS - Holanda dos Santos, Flávio; Lima Oliveira, Leane; Sousa, Raimundo (Revista Gênero e Interdisciplinaridade, 2026)
This article deals with the management at EMEF Ana Fortunato da Silva, in the municipality of Vitória do Xingu-PA. The objective was to analyze the implications of democratic school management, which enables the participation of the school community. To carry out this analysis, we had as reference the empirical management and access to documents recorded by the school. In the locus school, the management practice was developed from the perspective of the democratization of management. It was observed that school management can be implemented from a dialectical perspective, in which quantitative aspects cannot be superimposed on qualitative aspects, especially with regard to school autonomy and collective decisions, since reality is mediated and contradictory. The results of the analysis of this experience revealed that the practice of management, from the neoliberal - managerial - perspective, which is focused on results and quantitative educational indicators, can be overcome, as the school manager assumes the conception of management aligned with the dialectical perspective, which enables a management process, in fact, democratic and equitable. In this way, challenges of school management can be faced through an ethical and political posture, in which, indicators of managerial and pedagogical management coexist in intersection with the pillars of the process of democratization of management, providing the cultivation of a transformative posture, and learning with quality and equity, and more, it makes it possible to envision an emancipatory school management process, autonomous, transparent, with the participation of the school community in discussions and decision-making.